2011
DOI: 10.1016/j.brat.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Inferred threat and safety: Symbolic generalization of human avoidance learning

Abstract: a b s t r a c tSymbolic generalization of avoidance may underlie the aetiology and maintenance of anxiety disorders. The aim of the present study was to demonstrate inferred threat-avoidance and safety (non-avoidance) behaviours that occur in the presence of stimuli indirectly related to learned threat and safety cues. A laboratory experiment was conducted involving two symbolic stimulus equivalence relations consisting of three physically dissimilar stimuli (avoidance cues: AV1eAV2eAV3 and neutral cues: N1eN2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
46
1
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 49 publications
(84 reference statements)
10
46
1
10
Order By: Relevance
“…The fact that this discrimination continued into the probe phase using generalised stimuli, simply reflects this clear discriminative control and its extension through an effective generalisation procedure. This pattern has been widely observed in the literature on symbolic generalisation (e.g., Bennett, Hermans, Dymond, Vervoort, & Baeyens, in press;Dymond et al, 2007Dymond et al, , 2008Dymond et al, , 2011Gannon et al, 2011).…”
Section: Semantic Generalisation Cognition and Emotion 2015supporting
confidence: 66%
See 1 more Smart Citation
“…The fact that this discrimination continued into the probe phase using generalised stimuli, simply reflects this clear discriminative control and its extension through an effective generalisation procedure. This pattern has been widely observed in the literature on symbolic generalisation (e.g., Bennett, Hermans, Dymond, Vervoort, & Baeyens, in press;Dymond et al, 2007Dymond et al, , 2008Dymond et al, , 2011Gannon et al, 2011).…”
Section: Semantic Generalisation Cognition and Emotion 2015supporting
confidence: 66%
“…In contrast, avoidance responding to the safety cues (i.e., CSand GCS-) was at a rate of less than 2%. These rates of avoidance for conditioned and semantically related probe stimuli are comparable to the rates of conditioned and derived avoidance observed in studies on the transfer of avoidance via stimulus equivalence classes (i.e., "symbolic generalisation"; see Dymond et al, 2011). Those studies intended to model a process that likely occurs in the world outside the laboratory, facilitated by natural language categories, but using entirely abstract laboratory-created stimuli.…”
Section: Semantic Generalisation Cognition and Emotion 2015supporting
confidence: 64%
“…It remains possible, however, that our findings could have been influenced by this arrangement, and future studies that include learned and generalized stimuli at test are warranted (cf. Dymond et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Using a fear-irrelevant avoidance paradigm, Dymond et al (2011) showed that establishing avoidance with one stimulus in a network also produces avoidance of all indirectly related stimuli via symbolic generalization. Participants were first trained and tested for the formation of stimulus equivalence relations consisting entirely of abstract, arbitrary stimuli (labelled here, for purposes of clarity, with the alphanumerics, A1 = B1 = C1; A2 = B2 = C2).…”
mentioning
confidence: 99%
“…Augustson and Dougher (1997) were the first to show the symbolic-based generalized avoidance of stimuli that had no direct relational history with aversive events. Since then, Dymond, Schlund, Roche, Whelan, Richards, and Davies (2011) have extended these findings with a larger sample size to a similar operant avoidance paradigm involving aversive images and sounds as USs, while Dymond, Schlund, Roche, De Houwer, and Freegard (2012) showed that levels of symbolic generalization resemble those seen when avoidance is acquired indirectly, such as through verbal instructions (Rachman, 1977). Rhoden (2007, 2008) showed that the symbolic generalization of avoidance may be transformed in accordance with relations of "sameness" (i.e., equivalence) and "opposition."…”
Section: Symbolic Avoidance Generalizationmentioning
confidence: 91%